Two new «nosed» species of the genus Megalothorax (Collembola: Neelidae) from Russia - Panina, Kseniya; Babenko, Anatoly; Potapov, Mikhail (Zootaxa, 2022)
Two new species with forehead processes are described from the east of the European part and Western Siberia. Megalothorax processus sp. nov. has a long cuticular process extended at the tip. The cuticular process in M. roseus sp. nov. is formed by a group of four papillae. Two other species, M. potapovi Schneider, Porco & Deharveng, 2016 and M. sanctistephani Christian, 1998, with a “nose” in the frontal part of the head are known from the Far East of Russia and West Europe, respectively. The «noses» probably arise independently in the four species; their function is unclear. Apart from the form of the forehead processes M. processus sp. nov. differs from M. roseus sp. nov. by the shape of sensilla within sensory fields (flame-shaped vs. globular) and the absence of chaeta а0 (vs. present in M. roseus sp. nov.). Chaetotaxy of the frontal part of the head and abdomen is reduced in both species.